An empirical study of exploring the predictors of university teachers’ job satisfaction in Bangladesh: A structural equation modeling approach - Md Abdul Hye Zebon; Abdus Sattar; Md Sazzadur Ahamed (Heliyon)
This study aims to investigate the factors influencing job satisfaction among university teachers, considering various complex constructs such as salary and financial benefits, career growth and opportunities, relationships with colleagues, recognition, working environment, and leadership. Utilizing a quantitative cross-sectional research design, the present study was conducted in Bangladesh between August and December 2022. Encompassing 7 public universities and 12 private universities, the research purposively sampled 95 participants, adhering to a systematic and comprehensive approach to data collection. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical findings of the study revealed that career growth and opportunities (β = 0.225, t = 2.023, p < 0.10), leadership (β = 0.262, t = 1.757, p < 0.10), and relationships with colleagues (β = 0.166, t = 1.519, p < 0.10) had a significant positive impact on university teachers' job satisfaction. On the other hand, salary and financial benefits (β = 0.082, t = 0.823, p > 0.10), recognition (β = 0.02, t = 0.208, p > 0.10), and working environment (β = 0.14, t = 1.057, p > 0.10) had a positive but less significant impact on job satisfaction among university teachers. The overall findings provide valuable insights that can assist policymakers and stakeholders in implementing synchronized strategies to enhance job satisfaction among university teachers, ultimately leading to improved university teachers’ job performance.